Adherence to treatment guidelines and survival in older women with early-stage breast cancer in Denmark 2008–2012. (2nd July 2020) - Vogsen, Marianne; Bille, Camilla; Jylling, Anne Marie Bak; Jensen, Maj-Britt; Ewertz, Marianne; ,
Abstract: Objectives: The aims of this study were to compare patients 70 years or older with younger patients, to examine whether Danish patients with early-stage breast cancer aged 70 years or more received treatment according to guidelines, the reasons for deviating from the guidelines, and to analyze whether such deviations affected survival. Methods: From the Danish Breast Cancer Cooperative Group (DBCG) database we identified 23, 247 women diagnosed with early-stage breast cancer in Denmark from 2008 to 2012. 17, 391 were aged less than 70 years and 5856 were 70+ years. We reviewed medical charts of 441 patients aged 70+ years from Funen (a region of Denmark) to ascertain whether treatment was given according to the guidelines of DBCG and if not, the reason for deviating. Overall survival was analyzed by Cox proportional hazards models. Results: Up to age 80 years most women (94%) had surgery according to guidelines, decreasing to 41% in women aged 85+ years, the main reason for omitting surgery being patients' requests. Patients with breast cancer over the age of 80 years did not have an excess mortality compared with the general population in Funen. Compared with women who had surgery according to guidelines, women who did not have surgery had a significantly higher risk of dying with a hazard ratio (HR) of 8.38 (95% Confidence Intervals (CI) 4.46–15.8) if they were less than 80 years and HR = 2.56 (95% CI 1.63–4.01) if they were 80 years or more ( p  = .003 for interaction). Conclusions: Adherence to treatment according to guidelines decreases with increasing age, mainly for patients aged 80+ years. Our results suggest that surgery is important for the survival of patients aged less than 80 years.